Investigations of the inflow turbulence effect on rotational augmentation by means of CFD. Issue 2 (September 2016) - Bangga, Galih; Kim, Yusik; Lutz, Thorsten; Weihing, Pascal; Krämer, Ewald
Abstract: The present studies are addressed to gain more insights into the inflow turbulence effect on rotational augmentation using computational fluid dynamics. Three different cases were simulated and analysed focusing on the three-dimensional effects in the inboard blade region of a 10 MW generic wind turbine rotor. The evidence of rotational augmentation was presented and compared to two-dimensional simulations of the blade sections at consistent inflow conditions. Inflow turbulence has a very strong impact on the instantaneous blade loads and standard deviations, but the effect on the mean values is small. The amplitudes of the blade load fluctuations are amplified under turbulent inflow conditions and these are related to the blade passing frequency and the specified turbulence length scale at the inlet. Detailed examinations of these phenomena were performed and are presented in the present manuscript.